Physical and Geochemical Assessment of Limestone of Amran Group in Arhab Area-North Sana'a For Industrial Uses - Qaid, Ali M.; Alqubati, Naji; Al-Hawbani, Ali M. (Technium BioChemMed, 2021)
The present study is aimed to evaluate the potential of using limestone of Amran Group in Arhab area in different industries. X-ray diffraction pattern revealed that the limestone from Arhab is dominantly composed of calcite. The physical analysis showed that the bulk density is ranging from 2.4-2.88 g/cm3, water absorption 0.4-2.32%, void ratio 0.01- 0.06, whiteness 87.78-90.2 and specific surface area 3900-4650 cm².g-1. Based on the XRF results, limestones are pure and dominantly composed of calcium carbonate 97.52-99.06%. The concentration of major oxide: CaO is ranging from 54.70 to 55.50 wt%, SiO2 0.20 - 0.80 wt%, Al2O3 0.2 – 0.4 wt%, Fe2O3 0.13-0.28wt% and MgO 0.40-0.60 wt%. The other oxides are present with low concentration. Loss on ignition value varied from 42.40 to 43.16 wt% and exhibits strong positive correlation with CaO which attributed to the highest concentration of CaCO3. Geochemical data combined with Physical analyses data indicated that the limestone of Arhab area is suitable to be raw materials for various chemical industries such as paint, papers, ceramics, steel, pharmaceutical products and plastics after slightly modification of iron oxides in some special industries.